Printed paper waste as an alternative growing medium component to produce Brassica seedlings under nursery conditions - Chrysargyris, Antonios; Xylia, Panayiota; Akinci, Gorkem; Moustakas, Konstantinos; Tzortzakis, Nikos G. (My University, 2020)
Significant quantities of paper waste (PW) have been accumulated in recent years and the reuse/recycling of PW is required due to environmental concerns. In the present study, printed PW was used as a peat (P) substitute in growing medium for the Brassica seedlings production, considering recycling, sustainable agriculture, and partly peat replacement. Seeds of cauliflower, broccoli, and cabbage were seeded in growing media made of 0-10-30-50% PW. The addition of PW improved the growing media pH and mineral content, reduced the media aeration, and affected seed emergence. The PW decreased plant growth and the effects were more pronounced at 50% PW. The PW ≥ 30% decreased stomatal conductance, while chlorophyll fluorescence and content of chlorophylls decreased with high PW ratio, negatively affecting the plant physiology. The PW decreased plant sodium and iron and increased potassium, calcium, magnesium, and copper content. The PW increased antioxidant activity to a certain degree for cauliflower and cabbage and resulted in no change for broccoli, while polyphenols increased in cabbage seedlings. The addition of PW did not cause cellular damage as both lipid peroxidation and hydrogen peroxide production remained at low levels, maintaining low levels on the antioxidant enzymes (catalase, superoxide dismutase, peroxidase) metabolism. The present study shows that low PW content can partially replace peat for Brassica seedling production under a sustainable agriculture and environmentally friendly scheme.
Keywords: Printed paper waste; Peat; Brassica oleracea; Antioxidant activity; Enzymes; Recycling; Sustainable agriculture